Feature Reviews in Medicinal Chemistry - Mary J. Meegan (Pharmaceuticals)
This Special Issue of Pharmaceuticals (“Feature reviews in Medicinal Chemistry”) contains a series of reviews covering a broad selection of topics in Medicinal Chemistry, which are chosen to illustrate important recent results in this fast-evolving interdisciplinary research area that aims to improve human health by developing drugs to combat diseases [...]